Safety of simultaneous endoscopic submucosal dissection for two large colorectal neoplasias in the same patient - Kwak, Min Seob; Yang, Dong-Hoon; Hwang, Sung Wook; Bae, Jung Ho; Soh, Jae Seung; Lee, Seohyun; Lee, Ho-Su; Lee, Hyo Jeong; Park, Sang Hyoung; Ye, Byong Duk; Byeon, Jeong-Sik; Myung, Seung-Jae; et al. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Multiple large colorectal lesions requiring endoscopic submucosal dissection (ESD) are sometimes diagnosed during colonoscopy. We evaluated the feasibility and safety of ESD of two colorectal lesions in one session. Materials and Methods: The lesions of 16 patients who underwent two ESD procedures in a single session (double ESD group) from November 2009 to July 2014 were matched with those of 64 patients who underwent a single ESD procedure (single ESD group) based on the size and location of the lesion and presence of submucosal fibrosis. Results: The net ESD time per patient was longer in double ESD group than in single ESD group (104.0±36.2 vs. 59.1±39.2 min, p Conclusion: Compared with the single ESD, two simultaneous colorectal ESD procedures in a patient did not increase complications; the en bloc and curative resection rates were similar when performed a single ESD procedure and two simultaneous ESD procedures. Cite this article as: Kwak MS, Yang DH, Hwang SW, et al. Safety of simultaneous endoscopic submucosal dissection for two large colorectal neoplasias in the same patient. Turk J Gastroenterol 2018; 29: 183-90.